Pengembangan Kompetensi Aparatur Sipil Negara di Lingkungan Pemerintah Provinsi Kalimantan Timur - Sartika, Dewi; Kusumaningrum, Mayahayati (Jurnal Borneo Administrator, 2017)
This study aims to describe the competence development of civil servants in East Kalimantan Provincial Government based on Law Number 5 Year 2014 and the factors that influence it. With qualitative descriptive method, secondary data is collected through library research. Result of the research is the comparison of the personnel posture, senior officer ratio based on gender, and the accomodation of the local people which is still relatively small; Competence development is stillconsidered to be the domain of BKD and has not become a priority of regional government needs based on regional content. Competency development is still constrained by the lack of budget and managerial staff, the existence of inconsistentcentral policies that can not be followed by the region. Assessment is recomended toward the competencies which is relevant and required for senior leader level in order to arrange developed standards of managerial and socio-cultural competence. Competence development is not only concerned with the priority of accomodating local people to be apparatus, but also the vision of regional development. Capacity building should be based on the agency’s key strategic objectives and performance indicators. Dynamic leadership regeneration is needed as well as competency mapping with respect to gender sensitivity and priority of local people / regional content. Thus, innovative laboratories are required in each region to make change project of every high-level leader sustainable. Keywords: Competence Development, Civil Servant, East Kalimantan Province Government. Penelitian ini bertujuan untuk mendeskripsikan pengembangan kompetensi Aparatur Sipil Negara di Pemerintah Provinsi Kalimantan Timur, dari Undang-undang Nomor 5 Tahun 2014 serta faktor yang mempengaruhinya. Dengan metode deskriptif kualitatif, data sekunder dikumpulkan melalui penelitian kepustakaan. Hasil penelitian adalah perbandingan antara postur kepegawaian, rasio Pimpinan Tinggi (pimti) berdasar gender, dan akomodir putra daerah yang masih tergolong kecil; layanan publik menunjukkan inovasi pelayanan publik telah berjalan dengan lebih baik ditandai dengan reformasi pada sistem pelayanan publik. Pengembangan kompetensi masih dianggap menjadi ranah BKD dan belum menjadi prioritas kebutuhan pemerintah daerah berbasis regional content, pengembangan kompetensi masih terkendala dengan minimnya anggaran dan tenaga pengelola, adanya kebijakan pusat yang inkonsisten yang tidak mampu diikuti oleh daerah. Direkomendasikan assesment terhadap kompetensi yang dianggap relevan dan dibutuhkan oleh pimti, untuk selanjutnya disusun standar kompetensi manajerial dan sosio kultural. Pengembangan kompetensi tidak hanya memperhatikan prioritas putra daerah, juga visi pengembangan daerah. Penguatan kapasitas sebaiknya didasarkan pada sasaran strategis dan indikator kinerja utama instansi. Perlu dilakukan regenerasi kepemimpinan yang dinamis, pemetaan kompetensi dengan memperhatikan kepekaan gender dan prioritas putra daerah/regional content secara tepat sasaran. Perlu dibuat laboratorium inovasi di setiap daerah sebagai proyek perubahan berkelanjutan setiap pimpinan tinggi di unit kerjanya. Kata Kunci: Pengembangan Kompetensi, Aparatur Pemerintah, Pemerintah Provinsi Kalimantan Timur